Peran Kemandirian Belajar Sebagai Mediator Pengaruh Problem Based Learning Berbasis Canva Terhadap Pemahaman Konsep IPAS Siswa Kelas V Sekolah Dasar - Nasri Ahza, Akmal; Hariyanto; Kustiyowati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of Canva-based Problem Based Learning (PBL) on the understanding of IPAS concepts, the effect of Canva-based PBL on learning independence, the effect of learning independence on the understanding of IPAS concepts, and the role of learning independence as a mediator in the relationship between Canva-based PBL and the understanding of IPAS concepts among fifth-grade elementary school students. The research uses a quantitative approach with a quasi-experimental design of the Nonequivalent Control Group Design type. The research sample consists of 80 students, comprising 40 students in the experimental class and 40 students in the control class. Data collection was conducted using the IPAS concept understanding test and a learning independence questionnaire. Data were analyzed using descriptive statistics, prerequisite analysis tests, independent sample t-tests, and hierarchical regression to examine the mediation role. The research results show that Canva-based PBL significantly affects the understanding of IPAS concepts (β = 0.547; p < 0.001) and learning independence (β = 0.431; p < 0.001). Learning independence also significantly affects the understanding of IPAS concepts (β = 0.272; p = 0.009). The hierarchical regression results indicate that the influence coefficient of Canva-based PBL on the understanding of IPAS concepts decreased from β = 0.547 to β = 0.430 after the learning independence variable was included in the model, thus learning independence proved to play a role as a partial mediator. Additionally, the effect size value of 1.291 indicates that the implementation of Canva-based PBL has a strong influence on improving students' understanding of IPAS concepts. Therefore, the integration of PBL and Canva can be an effective learning alternative to enhance students' learning independence and understanding of IPAS concepts in elementary schools.